"Speaking with one voice": the Somali Retailers' Association - rights and xenophobia in Cape Town's townships - Hoeflich, Kathryn Leigh (Department of Social Development, 2015)
In the wake of extreme xenophobic violence, which swept South Africa in 2008, a group of Somali refugees resident in Cape Town formed the Somali Retailers’ Association (SRA) as a mutual support network made up of those who were targeted by xenophobes most: Somalis involved in informal sector trade in the townships. This study investigates the networks of targeted populations, analysing how this Association helps to mitigate the impact of xenophobia on the lives of its members.